2020
DOI: 10.3390/foods9091198
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Soy Isoflavones Nanoparticles Using Polymerized Goat Milk Whey Protein as Wall Material

Abstract: Soy isoflavones (SIF) are a group of polyphenolic compounds with health benefits. However, application of SIF in functional foods is limited due to its poor aqueous solubility. SIF nanoparticles with different concentrations were prepared using polymerized goat milk whey protein (PGWP) as wall material. The goat milk whey protein was prepared from raw milk by membrane processing technology. The encapsulation efficiencies of all the nanoparticles were found to be greater than 70%. The nanoparticles showed large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Results indicated that a part of the PNS was not encapsulated by PWP. Similar findings were reported by Tian et al [ 29 ], who found that encapsulation efficiency of soy isoflavones (SIF) in polymerized goat milk whey protein (PGWP) nanoparticles decreased with increasing SIF concentration. Researchers found that the curcumin showed higher encapsulation efficiency (93.1%) and oxidation stability using whey protein as the wall material [ 30 ].…”
Section: Resultssupporting
confidence: 89%
“…Results indicated that a part of the PNS was not encapsulated by PWP. Similar findings were reported by Tian et al [ 29 ], who found that encapsulation efficiency of soy isoflavones (SIF) in polymerized goat milk whey protein (PGWP) nanoparticles decreased with increasing SIF concentration. Researchers found that the curcumin showed higher encapsulation efficiency (93.1%) and oxidation stability using whey protein as the wall material [ 30 ].…”
Section: Resultssupporting
confidence: 89%
“…Additionally, similar binding constants in the order of 10 4 or 10 3 M −1 were described for numerous ligand‐protein complexes via fluorescence spectroscopic technique 30 . The increase of the binding constant with temperature increases indicated that the protein‐bound per unit of the fluorescent group increased 33 …”
Section: Resultsmentioning
confidence: 64%
“…30 The increase of the binding constant with temperature increases indicated that the protein-bound per unit of the fluorescent group increased. 33…”
Section: Fluorescence Quenching Mechanismmentioning
confidence: 99%
“…However, the O–H bands changed to 3286 cm −1 , 3390 cm −1 , 3310 cm −1 , and 3298 cm −1 in the RPH(F)-SIF, RPH(A)-SIF, RPH(N)-SIF, and RPH(T)-SIF spectra, respectively. And the phenolic hydroxyl groups were involved in the non-covalent interaction between RPH and SIF [ 35 ]. After the formation of nanoparticles, the various shifts of O–H band observed may be related to the secondary structure of the RPHs [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The influences of RPHs may be due to their different structure obtained by the hydrolysis of different enzymes, which was further affected the interaction between RPH and SIF. Because the absorption site of SIF is in the intestinal epithelial cells [ 35 ], the RPH-SIF needed to ensure sufficient release of SIF in the intestine. These results also suggested that a large amount of SIF from the RPH(F)-SIF delivery system will reach the colon, where it can exert a beneficial effect [ 45 ].…”
Section: Resultsmentioning
confidence: 99%